Numerical simulations and experimental results of tensile behaviour of hybrid composite shape memory alloy wires embedded structures. Issue 1 (September 2016) - Lebied, A.; Necib, B.; Sahli, M.; Gelin, J-C.; Barrière, T.
Abstract The shape memory alloys (SMA) possess both sensing and actuating functions due to their shape memory effect, pseudo-elasticity, high damping capability and other remarkable properties. Combining the SMA with other materials can create intelligent or smart composites. The epoxy resin composites filled with Ti-Ni alloys wires were fabricated, and their mechanical properties have been investigated. In this study, stress/strain relationships for a composite with embedded SMA wires are presented. The paper illustrates influence of the SMA wires upon changes in mechanical behaviour of a composite plate with the SMA components, firstly and secondly, the actuating ability and reliability of shape memory alloy hybrid composites.